A C-band Low-noise Frequency Synthesizer Based on Digital Phase-locked Loop - Yuan Xue-Lin; Zhu Chang; Yuan Nai-Chang (2007 5th International Conference on Microwave and Millimeter Wave Technology : proceedings : ICMMT 2007 : April 19-21, 2007, Guilin, China, 2007)
To reduce phase noise of microwave-band frequency synthesizer based on phase-locked loop(PLL), the method that the output signal of VCO is mixed with a Lo signal and the IF signal is detected, is proposed. Then, the compatible loop filter is designed. Finally, the experimental results prove that the phase noise of improved frequency synthesizer is greatly lower than that of directly phase-locked synthesizer.